Association of sex hormones and sex hormone-binding globulin with liver fat in men and women: an observational and Mendelian randomization study - Cai, Xinting; Thorand, Barbara; Hohenester, Simon; Prehn, Cornelia; Cecil, Alexander; Adamski, Jerzy; Zeller, Tanja; Dennis, Andrea; Banerjee, Rajarshi; Peters, Annette; Yaghootkar, Hanieh; Nano, Jana (Frontiers in Endocrinology, 2023)
Background: Sex hormones and sex hormone-binding globulin (SHBG) may play a role in fatty liver development. We sought to examine the association of various endogenous sex hormones, including testosterone (T), and SHBG with liver fat using complementary observational and Mendelian randomization (MR) analyses.The observational analysis included a total of 2,239 participants (mean age 60 years; 35% postmenopausal women) from the population-based KORA study (average follow-up time: 6.5 years). We conducted linear regression analysis to investigate the sex-specific associations of sex hormones and SHBG with liver fat, estimated by fatty liver index (FLI). For MR analyses, we selected genetic variants associated with sex hormones and SHBG and extracted their associations with magnetic resonance imaging measured liver fat from the largest up to date European genome-wide associations studies.In the observational analysis, T, dihydrotestosterone (DHT), progesterone and 17αhydroxyprogesterone (17-OHP) weereas in women, a positive association 4 of free T with FLI (β = 4.17, 95%CI: 1.35, 6.98) was observed. SHBG was inversely associated with FLI across sexes [men: -3.45 (-5.13, -1.78); women: -9.23 (-12.19, -6.28)]. No causal association was found between genetically determined sex hormones and liver fat, but higher genetically determined SHBG was associated with lower liver fat in women (β = -0.36, 95% CI:-0.61, -0.12).Our results provide suggestive evidence for a causal association between SHBG and liver fat in women, implicating the protective role of SHBG against liver fat accumulation.